Improvement in sinterability and phase stability of hydroxyapatite and partially stabilized zirconia composites - Evis, Zafer; Usta, Metin; Kutbay, Isil (Elsevier Sci Ltd, 2009)
Composites of hydroxyapatite with partially stabilized zirconia with MgO or MgF2 were pressureless sintered between 1000 degrees C and 1300 degrees C. The reactions and transformations of phases were verified by X-ray diffraction. For the hydroxyapatite and zirconia composites with MgO, calcium from the hydroxyapatite diffused into the zirconia phase, and the hydroxyapatite decomposed to tri-calcium phosphate at sintering temperatures higher than 1000 degrees C. Above about 1200 degrees C, CaZrO3 was formed. Composites containing the MgF2 decomposed slower than the composites with MgO, which was verified by the changes in the lattice volume of the hydroxyapatite left in these composites. Fluorine ions in MgF2 diffused into hydroxyapatite, which resulted in thermal stability at high sintering temperatures. Composites with MgF2 had higher hardness than those with MgO. The lowest porosity was found in a composite initially containing 10 wt% partially stabilized zirconia and 5 wt% MgF2. (C) 2008 Elsevier Ltd. All fights reserved.
Keywords: Apatite; Sintering; MgF2; Biomedical applications